Mineralogical characterization and speciation of sulfur, zinc and lead in pyrite cinder from Bergvik, Sweden. (August 2021) - Bendz, David; Tiberg, Charlotta; Kleja, Dan B.
Abstract: Roasting of sulfide ores to produce sulfuric acid began on an industrial scale in the middle 1800′s and is still used extensively worldwide. The residual, pyrite cinders, have commonly been disposed in the environment where they pose a potential and serious threat to aquatic life. In this project, two profiles in a pyrite cinder deposit in Bergvik, Sweden, have been sampled and a comprehensive mineralogical characterization have been carried out. The objectives were to investigate the composition and morphology of pyrite cinder grains and the speciation of sulfur, Pb and Zn in the solid phase. Scanning electron microscopy showed pyrite cinder grains with a core of the ore minerals pyrite and sphalerite enclosed in layers of iron oxides/hydroxides (mainly hematite). XANES analysis, supported by X-ray diffraction analysis, SEM-EDS and bulk element analysis, showed that content of the residual sulfur in the cinder is mainly sulfides, 55–80%, predominately sphalerite. The remaining mass of sulfur is assumed to be adsorbed or precipitated as secondary sulfate minerals, predominantly associated with the grain surfaces. Calculated saturation indexes indicated barite, anglesite and perhaps aluminite. EXAFS spectroscopy indicated that about half of the Zn was bound to O and half was bound to S. LCF analysis of EXAFS spectra indicated that the main Zn species were sphalerite (40–50%) and franklinite (10–20%). The remaining Zn was associated with iron oxides/hydroxides and Zn minerals like hydrozincite or possibly zinc oxides. SEM-EDS analysis showed Pb precipitate located on both the surface of the grains and in the interior as inclusions. The analytical interpretation indicated anglesite. Graphical abstract: Image 1 Highlights: Pyrite cinder grains commonly consist of an unreacted core of ore mineral. The residual sulfur in the cinder is 55–80% sulfide, predominately in sphalerite. Zn is mainly associated with sphalerite (40–50%) and franklinite (10–20%). Anglesite precipitates were detected.